SARS-CoV-2 Seroprevalence and Antibody Kinetics Among Health Care Workers in a Spanish Hospital After 3 Months of Follow-up. (11th November 2020) - Moncunill, Gemma; Mayor, Alfredo; Santano, Rebeca; Jiménez, Alfons; Vidal, Marta; Tortajada, Marta; Sanz, Sergi; Méndez, Susana; Llupià, Anna; Aguilar, Ruth; Alonso, Selena; Barrios, Diana; et al.
Abstract: Background: At the COVID-19 spring 2020 pandemic peak in Spain, prevalence of SARS-CoV-2 infection in a cohort of 578 randomly selected health care workers (HCWs) from Hospital Clínic de Barcelona was 11.2%. Methods: A follow-up survey 1 month later (April-May 2020) measured infection by rRT-PCR and IgM, IgA, and IgG to the receptor-binding domain of the spike protein by Luminex. Antibody kinetics, including IgG subclasses, was assessed until month 3. Results: At month 1, the prevalence of infection measured by rRT-PCR and serology was 14.9% (84/565) and seroprevalence 14.5% (82/565). We found 25 (5%) new infections in 501 participants without previous evidence of infection. IgM, IgG, and IgA levels declined in 3 months (antibody decay rates 0.15 [95% CI, .11–.19], 0.66 [95% CI, .54–.82], and 0.12 [95% CI, .09–.16], respectively), and 68.33% of HCWs had seroreverted for IgM, 3.08% for IgG, and 24.29% for IgA. The most frequent subclass responses were IgG1 (highest levels) and IgG2, followed by IgG3, and only IgA1 but no IgA2 was detected. Conclusions: Continuous and improved surveillance of SARS-CoV-2 infections in HCWs remains critical, particularly in high-risk groups. The observed fast decay of IgA and IgM levels has implications for seroprevalence studies using these isotypes. Abstract : SARS-CoV-2 prevalence in 578 health care workers increased from 11.2% at the COVID-19 pandemic peak to 14.9% 1 month later. IgM, IgG, and IgA levels declined over 3 months of follow-up with 68.33%, 3.08%, and 24.29% of seroreversions, respectively.